EKONOMI DAN PENDIDIKAN ANAK KELUARGA PETANI RUMPUT LAUT DI DESA NAIN SATU KECAMATAN WORI KABUPATEN MINAHASA UTARA - Edwin Reimon Tamengge; Maryam Lamadirisi; Y.D.A. Santie (Labor Program Studi Pendidikan Sosiologi, 2021)
The purpose of this study was to determine the economy and education of children of marine rumuput farmer families in Nain village, wori sub-district, North Minahasa district. This research uses qualitative research, with techniques such as observation and in-depth interviews, the data collection in this study uses internal validation and external validation. Sugiyono, 2010. From the results of this study, the economic life of seaweed farmers is different from other garden farmers, because working as a seaweed farmer has different difficulties for seaweed farmers, starting from the obstacles they face, namely the weather, to unexpected price drops that affect income. they. As a seaweed farming hunt, there are also obstacles faced, namely the results obtained and even not enough income to meet the economic demands of the family. Children's education is very important to pay attention to, but because of the limited costs of parents who work as seaweed farmers.